História de mulheres institucionalizadas - Pavan, Fábio José (Universidade do Vale do Rio do Sinos, 2007)
In the last decades, a clear process of demographic aging in the world population has been noticed. Regarding Brazil, the expectation is 32 million people over 60 years old constituting the sixth biggest aged population in the world. The aged internment in Institutions of Long Term Permanence (ILP) have increased. In this study, the theoretical background is based on studies about aging under the perspective of social sciences, total institution category and gender studies. We tried to understand how the process of institutionalization takes place, what the repercussions on the life of aged women are and how they face aging in asylums. This study was developed through an exploratory methodology and a qualitative approach. The field of research was an ILP for elderly, which gives attendance to 110 male and female aged people from Alto Uruguai Region, ages between 60 and 105 years old, where 80% were female. The subjects of the study were women, over 60 years old, who presented suitable oral expression. The da
Keywords: feminização da velhice; idosas institucionalizadas; envelhecimento; Ciências da Saúde